Sistem Pemantauan Pelacak Panel Surya Berbasis Internet of Things dengan Aplikasi Ponsel Pintar - Hadian Mandala Putra; Habibul Muzzamil; Ida Wahidah; Suhartini (Fakultas Teknik Universitas Hamzanwadi, 2026)
Solar energy is an environmentally friendly renewable energy source that has gained increasing attention due to its sustainability and widespread availability. The use of a solar tracking system capable of following the sun's movement can significantly improve the performance of solar panel systems. This study aims to develop an Internet of Things (IoT)-based monitoring system utilizing a smartphone application (Telegram on Android) to monitor and control a solar panel tracking system. The research employed a Research and Development (R&D) approach. The hardware components consisted of a tracking motor, Light Dependent Resistor (LDR) sensors, and a DC voltage sensor integrated with a solar panel system. The software component utilized a Telegram Bot as a platform for remote monitoring and control. The results demonstrated that the developed system was capable of performing real-time monitoring and control of the solar panel system through an internet connection. The main contribution of this study lies in the integration of an LDR-based solar tracking mechanism with a Telegram Bot-based monitoring and control system. Experimental results indicated that the proposed solar tracking system achieved a 23.18 % increase in average output voltage compared to a conventional static solar panel system. Furthermore, the output voltage remained more stable throughout the day because the solar panel was able to automatically follow the sun's trajectory. These findings indicate that the proposed system can enhance solar energy harvesting performance while providing a practical solution for remote monitoring and control.